Xun Pang, “Shared Challenges and Solutions: The Common Future of Comparative Politics and Quantitative Methodology” (Chinese Political Science Review, 2016)
This essay joins the discussion on ‘‘The Future of Comparative Politics’’ from a perspective of methodology, and argues that the challenges concerned in Schmitter’s essay are not endemic to comparative politics but shared ones in other research fields including quantitative methods. Recent trends and developments in quantitative methods show that quantitative and qualitative methods are increas- ingly integrated to jointly handle challenges with broad and profound impacts on the social sciences as a whole. This essay presents a brief introduction of the recent three revolutions in quantitative methods. The ‘‘Bayesian Revolution’’, the ‘‘Credibility Revolution’’, and the ‘‘Big Data Revolution’’ have fundamentally changed quantitative methods. The paper further displays that the challenges arising from the three revolutions are essentially the same ones with those in comparative politics, such as modeling complex interdependence, dealing with fuzzy concepts and the messy real world, and so on. Finally, the essay uses a few examples of some new analytical tools developed by quantitative methodologists to illustrate that qualitative knowledge and quantitative techniques should be seamlessly mixed to be innovative and powerful methods. All this points to a common future of compar- ative politics and quantitative methods.